2011
DOI: 10.1038/ncb2287
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1-phosphorylated CUEDC2 promotes spindle checkpoint inactivation and chromosomal instability

Abstract: Aneuploidy and chromosomal instability are major characteristics of human cancer. These abnormalities can result from defects in the spindle assembly checkpoint (SAC), which is a surveillance mechanism for accurate chromosome segregation through restraint of the activity of the anaphase-promoting complex/cyclosome (APC/C). Here, we show that a CUE-domain-containing protein, CUEDC2, is a cell-cycle regulator that promotes spindle checkpoint inactivation and releases APC/C from checkpoint inhibition. CUEDC2 is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 51 publications
3
75
0
Order By: Relevance
“…Phosphatase treatment does not cause the WT-IRAK2 to run at the same level as D431E-IRAK2. However, in the same assay, we detected obvious dephosphorylation of CUEDC2 as previously reported (34). These results indicated that the lower band of D431E-IRAK2 was not caused by dephosphorylation.…”
Section: Construction and Expression Of The Irak2 Wild Type And Its Dsupporting
confidence: 70%
“…Phosphatase treatment does not cause the WT-IRAK2 to run at the same level as D431E-IRAK2. However, in the same assay, we detected obvious dephosphorylation of CUEDC2 as previously reported (34). These results indicated that the lower band of D431E-IRAK2 was not caused by dephosphorylation.…”
Section: Construction and Expression Of The Irak2 Wild Type And Its Dsupporting
confidence: 70%
“…Second, an ATPdependent process has been implicated in SAC silencing (Teichner et al, 2011), raising the possibility that an ATPase cooperates with p31 comet in the disassembly process. In addition, CUEDC2 has very recently been implicated in dissociating Mad2 from Cdc20 (Gao et al, 2011). Finally, Cdc20 ubiquitylation and degradation also contributes to MCC turnover (Nilsson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…43,44 A substrate of mitotic CDK, CEUDC2, also binds to Cdc20 once phosphorylated, and this binding promotes the release of Mad2 from Cdc20 and the subsequent activation of APC/C Cdc20 . 45 However, no evidence indicates the direct link between these mechanisms and kinetochore attachment. It is likely that these mechanisms facilitate the robustness of SAC silencing once cells have initiated the SAC silencing process.…”
Section: The Disassembly Of the Mitotic Checkpoint Complex MCCmentioning
confidence: 99%